Petrographic and Lithofacies of Injana Formation Berman Inticline Northern Iraq - Amaar J. Mohammed Al-Taiiy (Tikrit Journal of Pure Science, 2023)
This study is including Petrographic and Lithofacies investigation of Injana Formation North Iraq. The Formation composed of succession of sandstone, siltstone and claystone cycles. The grain size analysis and indicated that the sandstone composed of medium to coarse grains, minor percent silt and clay. The petrographic indicated that the quartz with percent monocrystalline (11-30%) and polycrystalline (4-10%) type , while the feldspar forming mostly of Plagioclace feldspar (2-7.88%) and K-feldspar (5.20-11%). The rocks and fragments mostly of carbonate with percent (15.20- 22.20%) derived from outcrop rocks especially  from Fatha and Pilaspi Formation in the area. The recognized clay mineral are; Montmorellonite, palygorskite, kaolinite and chlorite